The Advantages of Cooperative Educational Technologies in The Domain of Oral Literacy - Berdiyeva Nilufar Ibodullayevna (Scientific Trends, 2024)
This article endeavors to examine the merits of collaborative educational technologies within the realm of oral literacy. It seeks to explore the application of contemporary cooperative educational technologies in fostering oral literacy competencies among students. Through an in-depth exploration of existing literature and empirical investigations, this research aims to discern the advantages associated with the utilization of cooperative educational technologies for the advancement of oral literacy, and its subsequent impact on students' language proficiency and oral communication acumen. Employing a mixed-method research approach, encompassing classroom observations, educator interviews, and student surveys, the research methodology is designed to provide a comprehensive understanding of the effectiveness of cooperative educational technologies in augmenting oral literacy skills. The section dedicated to analysis and results will articulate the study's findings, offering valuable insights into the efficacy of these technologies in elevating oral literacy. The concluding segment will encapsulate the primary discoveries and furnish recommendations for educators to harness cooperative educational technologies effectively in the cultivation of oral literacy skills.
Keywords: Uzbek culture, primary nature, holistic linguistic, oral literacy, methodologies, communication skills, theoretical framework.